2019
DOI: 10.1002/pssb.201800574
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Visible‐Light‐Induced Photocatalytic Activity of SrTiO3 Co‐Doped With Os and N: A GGA + U Investigation

Abstract: A systematic investigation based on spin-polarized DFT þ U has been carried out to study the electronic structure of charge compensated (Os, 2N)codoped SrTiO 3 as compared with that of pure SrTiO 3 , Os-doped SrTiO 3 , Ndoped SrTiO 3 , and charge non-compensated (Os, N)-codoped SrTiO 3 . The calculated band gap of pure SrTiO 3 is improved to 3.22 eV using GGA þ U method by choosing appropriate U values, which is in good agreement with the experimental value (3.25 eV). Although charge non-compensated codoping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…1(a), with lattice constants of a ¼ b ¼ c ¼ 3.905Å, b ¼ 90.00 are consistent with the experimental results found by Nelmes et al 64 For comparison, other experimental and theoretical lattice constants along with the band gap are listed in Table 1. 54,55,65,66 The band structure of cubic SrTiO 3 is shown in Fig. 2(a), and the calculated indirect band gap of 3.252 eV is very close to the experimental data of 3.22-3.25 eV at room temperature.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…1(a), with lattice constants of a ¼ b ¼ c ¼ 3.905Å, b ¼ 90.00 are consistent with the experimental results found by Nelmes et al 64 For comparison, other experimental and theoretical lattice constants along with the band gap are listed in Table 1. 54,55,65,66 The band structure of cubic SrTiO 3 is shown in Fig. 2(a), and the calculated indirect band gap of 3.252 eV is very close to the experimental data of 3.22-3.25 eV at room temperature.…”
Section: Resultssupporting
confidence: 72%
“…To obtain the ideal band-structure, in addition to the d orbitals in transition metals (U d ), a few theoretical studies of the +U effect on p orbitals (U p ) in oxygen have been discussed and has been shown to be crucial in oxides. [51][52][53][54][55] Therefore, in this work, the GGA+U p +U d method is used to best describe the localized transition and generate the most reliable result of band gap of SrTiO 3 , with the U p (4.20 eV) on O 2p and U d (5.95 eV) on Ti 3d. On-the-y generated (OTFG) ultraso pseudopotentials are employed to describe the interactions of ionic core and valance electrons.…”
Section: Details Of the Dft Simulationsmentioning
confidence: 99%
“…The indirect spindown band gap is about 1.75 eV within U d ¼ 4 eV, which is very close to the band gap (1.86 eV) calculated by the HSE hybrid density functional. 36 Therefore, for a better description of the localized transition, we used the on-site repulsion U eff ¼ 2.3 eV and 4 eV on the Ti 3d and Mo 4d states as in previous theoretical investigations, 35,37,38 and the U of the O 2p states was set to 8 eV. Spin-polarized calculations were performed for pure and different doped SrTiO 3 systems.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the optical properties of pristine and doped STO systems, the optical absorption coefficient is also calculated based on the electronic structure. [23,26] The supercell method is used to simulate the isolated defect for Al, N doping in STO lattice.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Thus, charge-compensated codoping is a better approach to reduce the bandgap and enhance the optical response, in the sense that electrons of the transmitter and recipient ions could compensate for one other to avoid the recombination centers. [23][24][25][26][27][28][29][30] For example, Liu [23] found that Ta and N codoping could reduce the recombination center while shorten the bandgap. Miyauchi [24] discovered that 0.5% La and N codoping boosted STO's activity.…”
Section: Introductionmentioning
confidence: 99%